Vertical–axial two–rotor wind power units Bidarrieus-1 - Yershin, Sh.; Yershina, A.K.; Ydyryssova, A.А. (Ye.A.Buketov Karaganda State University Publishing house, 2017)
The article is devoted to problems of modern wind energy. The technical characteristics and advantages of the two-rotor wind powers Bidarrieus have been described. The design concept and principle of operation of original vertically axial two-rotor semi-industrial specimens of Bidarrieus-1 are shown. It is proposed to use the independent principle of operation of rotating shafts connected to a wind turbine, as a distinctive feature of the design of this power unit. This original design of Bidarrieus-1 allows obtaining a high coefficient of wind energy use.
Keywords: two-rotor wind powers; Darrieus; Bidarrieus; vertically axial wind turbine; semi-industrial specimen; wind power utilization factor